Dysregulated CD4+ T Cells and microRNAs in Myocarditis - Wang, Jing; Han, Bo (Frontiers in Immunology, 2020)
Myocarditis is a polymorphic disease complicated with indeterminate etiology and pathogenesis, and represents one of the most challenging clinical problems lacking specific diagnosis and effective therapy. It is caused by a complex interplay of environmental and genetic factors, and causal links between dysregulated microribonucleic acids (miRNAs) and myocarditis have also been supported by recent epigenetic researches. Both dysregulated CD4+ T cells and miRNAs play critical roles in the pathogenesis of myocarditis, and the classic triphasic model of its pathogenesis consists of the acute infectious, subacute immune, and recovery/chronic myopathic phase. CD4+ T cells are key pathogenic factors underlying the development and progression of myocarditis, and the effector and regulatory subsets respectively promote and inhibit autoimmune responses. Furthermore, the reciprocal interplay of these subsets influences the pathogenesis as well. Dysregulated miRNAs along with their mRNA and protein targets have been identified in heart biopsies (intracellular miRNAs) and body fluids (circulating miRNAs) during myocarditis. These miRNAs show phase-dependent changes, and correlate with viral infection, immune status, fibrosis, destruction of cardiomyocytes, arrhythmias, cardiac functions and outcomes. Thus, miRNAs are promising diagnostic markers and therapeutic targets in myocarditis. In this review, we review myocarditis with an emphasis on its pathogenesis, and present a summary of current knowledge of dysregulated CD4+ T cells and miRNAs in myocarditis.